2019
DOI: 10.36497/jri.v39i3.62
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalens of Ototoxicity in Drug Resistance Tuberculosis Patients and The Associated Factors at Persahabatan General Central Hospital

Abstract: Background: The treatment of drug resistance tuberculosis needs second line injection antituberculosis drug that associated with irreversible ototoxic. The aim of this study is to know the prevalence of ototoxicity in tuberculosis drug resistance patients and the contributing factors. Methods: This is a cross sectional study among drug resistance TB patients who receive kanamysin or capreomycin as a part of drug regimen during intensive phase in January to September 2017 at Persahabatan hospital. Ototoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Out of seven studies, three studies reported the history of previous TB treatment. A study by Rahmawati et al, reported that in MDR-TB patients, the most common of the previous TB was TB category 1 (59,7%), category 1 and 2 (36,1%) (Rahmawati et al, 2019).…”
Section: Key Study Characteristicsmentioning
confidence: 99%
“…Out of seven studies, three studies reported the history of previous TB treatment. A study by Rahmawati et al, reported that in MDR-TB patients, the most common of the previous TB was TB category 1 (59,7%), category 1 and 2 (36,1%) (Rahmawati et al, 2019).…”
Section: Key Study Characteristicsmentioning
confidence: 99%